2019
DOI: 10.1016/j.curtheres.2019.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Health-Related Quality of Life Among Patients with Type II Diabetes Mellitus Who Are Insulin Users: A Multidimensional Model

Abstract: Background Diabetes Mellitus is a progressive, chronic and multifactorial endocrine disorder characterized by elevated serum glucose levels. It has a direct effect to social and health related quality of life. Objective This study aimed to determine the health-related quality of life among patients with type II diabetes mellitus (T2DM) using insulin therapy. Methods Cross-sectional observational study design was used to collect data from Mala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…Results from regression model indicated that those suffering from diabetes complications were more likely to report lower HRQoL. This result is in line with other recent studies in Vietnam and other countries ( Arifin et al, 2019 ; Gillani et al, 2019 ; Pham et al, 2020 ). These diabetes complications have the potential to add significant health and finance burdens, and have been associated with diminished HRQoL in adults ( Wexler et al, 2006 ).…”
Section: Discussionsupporting
confidence: 90%
“…Results from regression model indicated that those suffering from diabetes complications were more likely to report lower HRQoL. This result is in line with other recent studies in Vietnam and other countries ( Arifin et al, 2019 ; Gillani et al, 2019 ; Pham et al, 2020 ). These diabetes complications have the potential to add significant health and finance burdens, and have been associated with diminished HRQoL in adults ( Wexler et al, 2006 ).…”
Section: Discussionsupporting
confidence: 90%
“…[ 2 ] The health-disease burden showed increasing trends over the past decade[ 2 ] and to improve health-related quality of life, along with diabetic care, extensive monitoring guidelines should also be implemented. [ 1 2 3 4 5 ] Literature showed dominant prevalence of type 2 diabetes mellitus (T2DM) over type 1 diabetes mellitus (T1DM) all around the world. [ 1 4 , 5 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 2 3 4 5 ] Literature showed dominant prevalence of type 2 diabetes mellitus (T2DM) over type 1 diabetes mellitus (T1DM) all around the world. [ 1 4 , 5 ]…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations